O-Glycosylation regulates polarized secretion by modulating Tango1 stability. - Zhang, L.; Syed, Z.A.; van Dijk Härd, I.; Lim, J.M.; Wells, L.; Ten Hagen, K.G. (Proceedings of the National Academy of Sciences of the United States of America, 2014)
Polarized secretion is crucial in many tissues. The conserved protein modification, O-glycosylation, plays a role in regulating secretion. However, the mechanisms by which this occurs are unknown. Here, we demonstrate that an O-glycosyltransferase functions as a novel regulator of secretion and secretory vesicle formation in vivo by glycosylating the essential Golgi/endoplasmic reticulum protein, Tango1 (Transport and Golgi organization 1), and conferring protection from furin-mediated proteolysis. Loss of the O-glycosyltransferase PGANT4 resulted in Tango1 cleavage, loss of secretory granules, and disrupted apical secretion. The secretory defects seen upon loss of pgant4 could be rescued either by overexpression of Tango1 or by knockdown of a specific furin (Dfur2) in vivo. Our studies elucidate a novel regulatory mechanism whereby secretion is influenced by the yin/yang of O-glycosylation and proteolytic cleavage. Moreover, our data have broader implications for the potential treatment of diseases resulting from the loss of O-glycosylation by modulating the activity of specific proteases.